Student’s Challenge Speaking Skill Toward Merdeka Curriculum By Using Project Based Learning In Juniour High Skill - Subhan, Ulya Maulani; Subhan, Roni (UAS PRESS, 2024)
This study explores the challenges and opportunities associated with developing speaking skills among junior high school students within the framework of the Merdeka Curriculum through Project-Based Learning (PBL). The purpose of this research is to know the character building of student’s speaking skill and to find out the student ability who are able in speaking. This study employs a descriptive qualitative research to explore the challenges faced by junior high school students in developing their English-speaking skills through Project-Based Learning (PBL) under the Merdeka Curriculum. The observation is doing in the second grade of Juniour High School. The data collection was carried out by observation and using video to test the speaking ability. The findings reveal that while students showed notable improvement in their speaking skills when engaged in PBL, several challenges hindered its full effectiveness. These challenges include students' initial reluctance to participate in speaking activities due to anxiety and a lack of confidence, particularly among those with lower English proficiency. Additionally, time constraints within the school curriculum made it difficult for teachers to balance content coverage with providing adequate speaking practice.